2021
DOI: 10.2147/ijn.s283164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anti-Glaucoma Drugs on Uptake of Extracellular Vesicles by Trabecular Meshwork Cells

Abstract: Background Extracellular vesicles (EVs) are capable of manipulating cellular functions for the maintenance of biological homeostasis and disease progression, such as in glaucoma disease. These nano-particles carry a net negative surface charge under physiological conditions that can contribute to EVs:EVs interaction and their uptake by target cells. Purpose To investigate the effect of glaucoma drugs on EVs physicochemical characters and the implications for their uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…An imaging flow cytometer study used to track the kinetics of NPCE EVs internalization ratio by TM cells resulted in a maximal uptake ratio of EVs to TM cells after 24 h [ 9 ]. Since our previous data demonstrated that EVs are mediators of the NPCE-TM cells communication at early time points, in the present study we examined the effects of loaded EVs with siRNA on TM cells at an earlier time point of 24 h rather than 48 h, 72 h, or 96 h. Tracking the expression of Wnt-TGFβ2 proteins in TM cells exposed to NPCE EVs, led to a significant attenuation of the expression levels of all examined proteins ( Figure 6 ) as was previously shown [ 9 , 40 , 41 ]. Targeting SMAD7 in TM cells with electroporated EVs, eliminated the decrease of both β-Catenin ( Figure 6 D) and pGSK3 ( Figure 6 C) proteins levels observed upon addition NPCE EVs to TM cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…An imaging flow cytometer study used to track the kinetics of NPCE EVs internalization ratio by TM cells resulted in a maximal uptake ratio of EVs to TM cells after 24 h [ 9 ]. Since our previous data demonstrated that EVs are mediators of the NPCE-TM cells communication at early time points, in the present study we examined the effects of loaded EVs with siRNA on TM cells at an earlier time point of 24 h rather than 48 h, 72 h, or 96 h. Tracking the expression of Wnt-TGFβ2 proteins in TM cells exposed to NPCE EVs, led to a significant attenuation of the expression levels of all examined proteins ( Figure 6 ) as was previously shown [ 9 , 40 , 41 ]. Targeting SMAD7 in TM cells with electroporated EVs, eliminated the decrease of both β-Catenin ( Figure 6 D) and pGSK3 ( Figure 6 C) proteins levels observed upon addition NPCE EVs to TM cells.…”
Section: Discussionsupporting
confidence: 63%
“…In earlier studies in our lab, involving human NPCE-derived exosomes’ characterization [ 37 , 38 ], we were able to provide evidence for their role as signaling mediators of the Wnt signaling pathway in TM cells. These EVs demonstrated a specific uptake mechanism [ 39 ] influenced by particle interactions [ 40 , 41 ]. We suggested that these native biological nanoparticles mediate the communication between NPCE and TM cells by ECM remodeling [ 42 ], supporting a physiological role in IOP regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show the increase of zeta potential of EVs enhances its endocytosis by neighboring cell. [21,34] When neutrophils were treated with PMA, NETs generated, and released histone with positive charge. Liposomes (++) have repulsive force with histone.…”
Section: Nets Attract Apovs In Septic Mice Via Electrostatic Charge I...mentioning
confidence: 99%
“…Eye drops are a fundamental type of topical administration due to their ease of application, favorable cost, and good patient consistency [35]. The typical retention time of eye drops administered topically in the pre-corneal tear film is about 1 min.…”
Section: Eye Drops and Eye Ointmentsmentioning
confidence: 99%